Art and algae: an ocean intimacy. A story in four parts - Josie Iselin (Applied Phycology)
I am a photographer, author and designer of many books, with my last few focusing on the world of seaweed and kelp. My most recent book, The Curious World of Seaweed, is the basis for a travelling exhibition of prints by the same name. I am the co-director of Above/Below, a campaign working to bring the recognition afforded the forests on land to the kelp forests below the ocean’s surface. Above/Below’s signature effort is a web-based book titled The Mysterious World of Bull Kelp. Released in November 2023, it has been accessed by over 10,000 kelp-curious learners with ocean educators, kelp researchers, and graduate students interested in the convergence of art and science using the website frequently. For over 20 years I have used my flatbed scanner and computer exclusively for generating imagery. Synthesizing the scientific stories of the Pacific and Atlantic rocky coasts, beaches, and nearshore waters is my overriding passion, bringing thoughtfulness and stewardship to these extraordinary places of discovery. This essay, Art & Algae: An Ocean Intimacy, concludes that artmaking is essential for our human relationships with seaweed and kelp so that understanding of these organisms can flourish. It is told as a diaristic account of four instances of place-based, algal artmaking.